2017
DOI: 10.1093/infdis/jix500
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Spatiotemporal Dynamics of Enterovirus A71 Subgenogroups in Vietnam

Abstract: This study highlights a persistent transmission network of EV-A71, with specific Asian countries seeding other countries in the region and beyond, emphasizing the need for improved EV-A71 surveillance and detailed genetic and antigenic characterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
21
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 42 publications
6
21
1
5
Order By: Relevance
“…The large outbreaks of HFMD caused by the subgenotype C4 were reported in Asia, including China in 2012, southern Vietnam in 2011 and Thailand in 2008‐2009 . In southern Vietnam, HFMD outbreaks were reported with cocirculation of subgenotype C4 and C5 in 2011 . Our study also demonstrated that the subgenotype B5 virus was closely related to variants that caused HFMD outbreaks in southern Vietnam and in Thailand .…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…The large outbreaks of HFMD caused by the subgenotype C4 were reported in Asia, including China in 2012, southern Vietnam in 2011 and Thailand in 2008‐2009 . In southern Vietnam, HFMD outbreaks were reported with cocirculation of subgenotype C4 and C5 in 2011 . Our study also demonstrated that the subgenotype B5 virus was closely related to variants that caused HFMD outbreaks in southern Vietnam and in Thailand .…”
Section: Discussionsupporting
confidence: 59%
“…The previous studies demonstrated a significant association between the genotypes/subgenotypes and pathogenic proper- 25 In southern Vietnam, HFMD outbreaks were reported with cocirculation of subgenotype C4 and C5 in 2011. 10,11 Our study also demonstrated that the subgenotype B5 virus was closely related to variants that caused HFMD outbreaks in southern Vietnam and in Thailand. 9 EV71 strains 8 18 22 30 31 43 58 77 87 98 121 134 145 167 172…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations